Correction: Corrigendum: In situ targeted MRI detection of Helicobacter pylori with stable magnetic graphitic nanocapsules - Yunjie Li (Nature Portfolio, 2017)
Nature Communications 8: Article number: 15653 (2017); Published: 15 June 2017; Updated: 30 August 2017 Supplementary Fig. 4 of this Article contains errors. Supplementary Fig. 4c shows the T2-weighted phantom images in reverse order, and Supplementary Fig. 4d is a duplicate of Fig. 3d. The corrected version of Supplementary Fig.